Strategi Pengembangan Bisnis UMKM Sambal Pecel Khas Magetan Dalam Rangka Menciptakan Competitive Advantages - Dedy Kunhadi (Shofanah Media Berkah, 2023)
Small and Medium Enterprises (SMEs) play a significant role as a fundamental pillar in the economy of a country or region. There are many challenges faced by the SME sector, including issues related to capital, management and production processes. economic growth in a society is reflected through the progress of the creative industry sector in the region, which depends on the implementation of competitive advantage strategies. Sambal pecel, as a special dish derived from peanuts, is a symbol of the identity of Magetan Regency. Sambal pecel is not only a complement to food such as rice or lontong, but also represents a challenge for Sambal pecel SMEs to continue to exist. In an effort to maintain competitiveness, Sambal Pecel MSMEs need to formulate strategies and advantages that excel in competition with other pecel chili businesses. The results of this study are 12 Strengths Opportunities (SO) Strategies, 12 Weaknesses Opportunities (WO) Strategies, 11 Strengths Threats (ST) Strategies, and 12 Weaknesses Threats (WT) Strategies.